Analisis Pemeriksaan CT Scan Leher Dengan Kontras Pada Kasus Tumor Tiroid Di Instalasi Radiologi RSUD Provinsi NTB - Rahmah Rahmah; Kadek Yuda Astina; I Bagus Gede Dharmawan (Journal of Educational Innovation and Public Health, 2023)
Background: Thyroid tumors are abnormal growths of the thyroid gland, which can be benign or malignant tumors such as papillary, follicular, medullary or anaplastic types (Aldino, 2018). CT scan of the neck according to (Lee at al, 2016) The contrast media used consists of 80 ml of non-ionic contrast media followed by 20 ml of saline given through the antecubital vein using a power injector and a 20 gauge intravenous catheter at a speed of 2.5- 3.0 ml/sec. According to (Yang et al., 2016) 80-100 ml of 300 mg/L omnipaque contrast media is injected through the cubital vein at a rate of 2.7-3.0 mL/s. And according to (Deng et al., 2019), 80 ml of iopromide (300 mgl/mL) contrast media is injected intravenously at a rate of 3 ml/sec. The aim of this research is to determine the procedure for a CT scan of the neck with contrast in cases of thyroid tumors in the radiology installation at the NTB Provincial Regional Hospital. Method: The type of research carried out is qualitative research with a case study approach. Data were collected by observation, interviews with one radiologist and three radiographers and documentation. Data collection was carried out from June to July 2023. Data analysis was carried out using an interactive model system. Results: This study shows that the contrast media used in CT scans of the neck uses 50 ml contrast media on the grounds that 50 ml contrast media can confirm the diagnosis because in the case of tumors in the thyroid you only want to see whether there is enhancement of the tumor. And the contrast media injection is carried out manually by a radiology nurse on the grounds that it is sufficient to confirm the diagnosis if it is carried out with proper control so that the examination is simpler and the processing time is faster. Conclusion: There is a difference in the CT scan of the neck between theory and the NTB provincial hospital where in theory Lee et al (2016) explains that 80 ml of contrast media is used and an injector is used at a speed of 2.5-3.0 ml/s while the provincial hospital NTB uses 50 ml contrast media and is injected manually by a radiology nurse on the grounds that this can confirm the diagnosis.